Aid for trade in developing countries: complex linkages for real effectiveness - (:unkn) unknown (My University, 2009)
Aid for trade is intended to support the integration of developing countries into the world trading system. Although this form of aid is being hailed as a promising new development tool, it lacks the strategic dimension that it needs if it is to be truly effective and fulfill donors' policy commitments. From a theoretical perspective, this paper presents the various aid-for-trade categories and analyzes the linkages between foreign direct investment, aid for trade and development. It also presents a typology of trade-related needs for a panel of countries, to serve as a guide for donors in formulating their aid supply strategies. This typology reveals a number of disparities between countries and regions, as well as a low level of regional integration. Trade-related needs are particularly significant in West Africa and East Africa, and substantial in the infrastructure sector. This paper also stresses the importance of refining the formulation of actual demand by beneficiaries, structuring the aid supply in accordance with donors' specific areas of expertise and enhancing coordination among the various stakeholders, both public and private. Lastly, further trade liberalization will not by itself suffice to generate strong growth and improve the geographical and sectoral distribution of foreign direct investment. Factors such as political stability, the business climate, physical infrastructure, institutions and human capital also play a fundamental role. Of particular importance is the coherence of trade, sectoral, macroeconomic and tax policies, not only within each country and region but also between industrialized and developing countries. / L'aide au commerce, présentée comme un nouvel outil de développement prometteur, vise à soutenir l'intégration commerciale des pays en développement. Il manque néanmoins à cette aide, pour asseoir son efficacité et respecter les engagements politiques des donateurs, une dimension stratégique. D'un poin
Keywords: African Research